The evolution of Nigerian cybercrime: Two case studies of UK-based offender networks - Lusthaus, Jonathan (European journal of criminology, 2025)
Thus far, the literature on cybercrime has focussed on ?cyber-dependent?, rather than ?cyber-enabled? crime. This has meant the emphasis has been on online settings, technical offences, and Western cybercriminals. This paper seeks to partially address these gaps through focussed qualitative case study analyses of two Nigerian offender networks based in Europe, which were both engaged in cyber-enabled fraud and had a strong offline component. We seek to answer two key research questions: (1) How have Nigerian cybercriminal networks evolved over time? (2) How do Nigerian cybercriminal networks operate abroad, particularly within a European context? Our findings include that, over time, Nigerian offenders have adopted several cybercriminal business models, and that these operations are increasingly sophisticated and engaging with some more technical components of cybercrime. Notably, these offenders were mobile, which suggests that cybercrime networks can be transnational through migration and the formation of new offline/local hubs across the world, rather than through virtual means alone.